Did Italy Need More Labour Flexibility? - Marta Fana; Dario Guarascio; Valeria Cirillo (Intereconomics, 2016)
The dramatic impact of the 2008 crisis on the Italian economy led to policy responses including structural reforms and labour market liberalisation to reverse the worrisome output and employment trends. A key action by the Italian government, the evocatively named Jobs Act of 2014, has deeply changed Italian industrial relations. The Jobs Act has introduced a new contract type that substantially limits workers' rights to reinstatement in case of fi rms invalidly fi ring them. This article frames the Jobs Act within the overall liberalisation process begun in Italy in the 1990s, providing an initial evaluation of its impacts. Using detailed data sources, we show that the expected boost in employment cannot be detected, the share of temporary contracts over open-ended ones has increased and the number of part-time contracts has risen. This evidence suggests that the Jobs Act is failing to achieve its main goals.
Keywords: 330; Arbeitsmarktflexibilität; Arbeitsbeziehungen; Wirkungsanalyse; Italien